Clinical, biochemical and genotypical characteristics in biotinidase deficiency - Akgun, Abdurrahman; Sen, Askin; Onal, Hasan (Walter de Gruyter Gmbh, 2021)
Objectives: Hypotonia, lethargy, eczema, alopecia, conjunctivitis, ataxia, hearing loss, optic atrophy, cognitive retardation, and seizures can occur in patients with biotinidase deficiency, and it is inherited as autosomal recessive. The aim of this study was to evaluate the cases followed up with the diagnosis of biotinidase deficiency in our unit, in terms of clinical, biochemical and genetic analyses. Methods: A total of 112 cases followed up in our centre with the diagnosis of biotinidase deficiency between August 2018-September 2020 were included in the study. Data were collected retrospectively. Results: A total of 112 cases (55.4% male, mean age: 2.2 +/- 2.8 years) diagnosed with biotinidase deficiency were evaluated. Diagnoses were made by newborn screening in 90.2% of the cases, by family screening in 4.5%, and by investigating symptoms in 5.4%. The most frequently (27.5%) detected mutations were c.1330G>C (p.D444H)/ c.1330G>C (p.D444H) homozygous mutation, followed by (13.0%) c.1330G>C (p.D444H)/c.470G>A (p.R157H) compound heterozygous mutation, and (13.0%) c.470G>A (p.R157H)/c.470G>A (p.R157H) homozygous mutation. Biotinidase enzyme levels were found to be higher in patients with the p.D444H homozygous mutation than patients with other mutations. Biotin treatment was started in all patients with enzyme deficiency. Conclusions: Since the treatment is inexpensive and easily available, it is vital to detect this disease before symptom onset, especially findings related to the central nervous system, hearing and vision loss. In patients diagnosed with enzyme deficiency, the diagnosis should be definitively confirmed by genetic analysis.
Keywords: biotinidase deficiency; BTD gene mutation; hearing loss; newborn screening; optic atrophy